The existence of solution of nonlinear problem of magnetization - Pranas Katauskis (Lietuvos Matematikos Rinkinys, 1999)
The kinetic equations describing the magnetization of a medium consisting of single-domain particles are investigated. The local existence of solution and its uniqueness is proved.